OP26 Risankizumab induces early clinical remission and response in patients with Moderate-to-Severe Crohn's Disease: Results from the phase 3 ADVANCE and MOTIVATE studies. (27th May 2021) - Schreiber, S W; Ferrante, M; Panaccione, R; Colombel, J F; Hisamatsu, T; Lim, A; Lindsay, J O; Rubin, D T; Sandborn, W J; Neimark, E; Song, A P; Liao, X; et al.
Abstract: Background: Present therapies leave an unmet need for early and effective treatment for patients with Crohn's disease (CD). Risankizumab (RZB), a humanized immunoglobulin G1 monoclonal antibody against the p19 subunit of interleukin-23, was evaluated as an induction therapy to induce early clinical remission and response in patients with moderate-to-severe CD in two double-blind, randomized, placebo (PBO)-controlled studies (ADVANCE [NCT 03104413 ] and MOTIVATE [NCT 03105128 ]). Methods: Patients with moderate-to-severe CD (CD Activity Index [CDAI] of 220–450, Simple Endoscopic Score for CD [SES-CD] ≥ 6 [≥ 4 for isolated ileal disease] excluding the narrowing component, and average daily [liquid/very soft] stool frequency [SF] ≥ 4 and/or average daily abdominal pain [AP] score ≥ 2) who had inadequate response or intolerance to conventional and/or biologic treatment (ADVANCE), or biologic treatment only (MOTIVATE) were randomised 2:2:1 (ADVANCE) or 1:1:1 (MOTIVATE) to receive intravenous RZB 600 mg, RZB 1200 mg, or PBO as induction therapy at weeks 0, 4, and 8. Clinical remission (per either CDAI or a composite of SF and AP criteria), clinical response (per CDAI criterion), and enhanced clinical response (per a composite of SF and AP criteria) were evaluated at weeks 4, 8, and 12 (endpoints defined in Figure 1 footnotes). Safety was assessed throughout the studies. Results: A total of 1419 patients from ADVANCE (N = 850) and MOTIVATE (N = 569) respectively, were randomised and included in the intention-to-treat population. In both studies, starting at week 4 (the first prespecified measurement), greater proportions of RZB 600 mg or RZB 1200 mg- vs PBO-treated patients achieved clinical remission per either CDAI ( P = .01/ P < .05) or SF/AP criteria ( P < .01/ P < .01), clinical response per CDAI criterion ( P = .001/ P < .01), and enhanced clinical response per SF/AP criteria ( P < .01/ P = .14) (Figure 1 ). For both RZB 600 mg and RZB 1200 mg, the efficacy and treatment effect increased through week 12 ( P ≤ .001/ P ≤ .001) (Figure 1 ). Treatment with RZB 600 mg or 1200 mg was well tolerated, and no new safety risks were identified. 1, 2 Conclusion: Induction therapy with both RZB 600 mg and 1200 mg intravenous resulted in significantly greater clinical remission and response vs PBO as early as week 4 and sustained through week 12 in patients with moderate-to-severe CD who had inadequate response or intolerance to conventional and/or biologic treatment. References: D'Haens G et al. ADVANCE study. Abstract presented at Digestive Disease Week 2021; 21–23 May 2021; Virtual. AbbVie In. (7 Jan 2021). Risankizumab (SKYRIZI®) Demonstrates Significant Improvements in Clinical Remission and Endoscopic Response in Two Phase 3 Induction Studies in Patients with Crohn's Disease [Press release]. Retrieved from https://news.abbvie.com/news/press-releases/risankizumab-skyrizi-demonstrates-significant-improvements-in-clinical-remission-and-endoscopic-response-in-two-phase-3-induction-studies-in-patients-with-crohns-disease.htm